Pengembangan Aplikasi Android untuk Monitoring Stok Beras berbasis Internet of Things - Ajiwicaksana, Bayu; Fachrie, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Indonesia plays a significant role, particularly in the agricultural sector. The agricultural sector also contributes to the development of social, economic, and trade sectors. One of the products of the agricultural sector is rice. Rice is considered a staple in Indonesian households, serving as a crucial dietary component. Given its essential nature, rice owners must monitor their rice stock to ensure its consistent availability. However, in order to ascertain the rice stock, the rice owner must physically inspect it. The rice owner must, of course, rely on their memory to recall the remaining rice. This approach is less effective due to the limitations of human memory. To address this issue, the development of an Android-based system utilizing IoT (Internet of Things) technology becomes imperative. This system can provide real-time information on rice stock, accessible anytime and anywhere through a smartphone application. Therefore, rice owners will no longer face difficulties in monitoring their rice stock, as the information can be conveniently accessed via a mobile application.